Percutaneous balloon compression under C-arm CT guidance for trigeminal neuralgia in patients with dural calcification: A case report - Yin, Ji; Liu, Zheng; Gong, Rui; Zhu, Li; Wang, Xingyuan (Interdisciplinary neurosurgery : Advanced techniques and case management, 2024)
C-arm computed tomography (CT)-guided percutaneous balloon compression (PBC) achieves intraoperative visualization, which allows for an intuitive display of the morphology and positional relationship between the balloon and the cranial base osseous structures. By promptly diagnosing variations or abnormalities in the cranial base structures and adjusting surgical strategies in a timely manner during the operation, precision treatment can be achieved. We report a rare case of diagnosing dural calcification in the cranial base during C-arm CT-guided PBC for trigeminal neuralgia.